Biographical Memoirs: Volume 60 - National Academy of Sciences (The National Academies Press, 1991)
Biographic Memoirs: Volume 60 contains the biographies of deceased members of the National Academy of Sciences and bibliographies of their published works. Each biographical essay was written by a member of the Academy familiar with the professional career of the deceased. For historical and bibliographical purposes, these volumes are worth returning to time and again.
Keywords: Biography and Autobiography

Biographical Memoirs: Volume 78 - National Academy of Sciences (The National Academies Press, 2000)
Biographic Memoirs: Volume 78 contains the biographies of deceased members of the National Academy of Sciences and bibliographies of their published works. Each biographical essay was written by a member of the Academy familiar with the professional career of the deceased. For historical and bibliographical purposes, these volumes are worth returning to time and again.
Keywords: Biography and Autobiography

Biographical Memoirs: Volume 90 - National Academy of Sciences (The National Academies Press, 2009)
Biographic Memoirs Volume 90 contains the biographies of deceased members of the National Academy of Sciences and bibliographies of their published works. Each biographical essay was written by a member of the Academy familiar with the professional career of the deceased. For historical and bibliographical purposes, these volumes are worth returning to time and again.
Keywords: Biography and Autobiography

Biographical Memoirs: Volume 44 - National Academy of Sciences (The National Academies Press, 1974)
Biographic Memoirs: Volume 44 contains the biographies of deceased members of the National Academy of Sciences and bibliographies of their published works. Each biographical essay was written by a member of the Academy familiar with the professional career of the deceased. For historical and bibliographical purposes, these volumes are worth returning to time and again.
Keywords: Biography and Autobiography

Biographical Memoirs: Volume 83 - National Academy of Sciences (The National Academies Press, 2003)
Biographic Memoirs Volume 83 contains the biographies of deceased members of the National Academy of Sciences and bibliographies of their published works. Each biographical essay was written by a member of the Academy familiar with the professional career of the deceased. For historical and bibliographical purposes, these volumes are worth returning to time and again.
Keywords: Biography and Autobiography

Biographical Memoirs: Volume 48 - National Academy of Sciences (The National Academies Press, 1976)
Biographic Memoirs: Volume 48 contains the biographies of deceased members of the National Academy of Sciences and bibliographies of their published works. Each biographical essay was written by a member of the Academy familiar with the professional career of the deceased. For historical and bibliographical purposes, these volumes are worth returning to time and again.
Keywords: Biography and Autobiography

Biographical Memoirs: Volume 80 - National Academy of Sciences (The National Academies Press, 2001)
Biographic Memoirs: Volume 80 contains the biographies of deceased members of the National Academy of Sciences and bibliographies of their published works. Each biographical essay was written by a member of the Academy familiar with the professional career of the deceased. For historical and bibliographical purposes, these volumes are worth returning to time and again.
Keywords: Biography and Autobiography

Biographical Memoirs: Volume 58 - National Academy of Sciences (The National Academies Press, 1989)
Biographic Memoirs: Volume 58 contains short biographies of deceased members of the National Academy of Sciences.
Keywords: Biography and Autobiography

Biographical Memoirs: Volume 89 - National Academy of Sciences (The National Academies Press, 2007)
On March 3, 1863, Abraham Lincoln signed the Act of Incorporation that brought the National Academy of Sciences into being. In accordance with that original charter, the Academy is a private, honorary organization of scientists, elected for outstanding contributions to knowledge, who can be called upon to advise the federal government. As an institution the Academy's goal is to work toward increasing scientific knowledge and to further the use of that knowledge for the general good. The Biographical Memoirs, begun in 1877, are a series of volumes containing the life histories and selected bibliographies of deceased members of the Academy. Colleagues familiar with the discipline and the subject's work prepare the essays. These volumes, then, contain a record of the life and work of our most distinguished leaders in the sciences, as witnessed and interpreted by their colleagues and peers. They form a biographical history of science in America—an important part of our nation's contribution to the intellectual heritage of the world.
Keywords: Biography and Autobiography

Biographical Memoirs: Volume 88 - National Academy of Sciences (The National Academies Press, 2006)
Biographic Memoirs Volume 88 contains the biographies of deceased members of the National Academy of Sciences and bibliographies of their published works. Each biographical essay was written by a member of the Academy familiar with the professional career of the deceased. For historical and bibliographical purposes, these volumes are worth returning to time and again.
Keywords: Biography and Autobiography

Memorial Tributes: Volume 23 - National Academy of Engineering (The National Academies Press, 2021)
This is the twenty-third volume in the series of Memorial Tributes compiled by the National Academy of Engineering as a personal remembrance of the lives and outstanding achievements of its members and foreign associates. These volumes are intended to stand as an enduring record of the many contributions of engineers and engineering to the benefit of humankind. In most cases, the authors of the tributes are contemporaries or colleagues who had personal knowledge of the interests and the engineering accomplishments of the deceased.
Keywords: Biography and Autobiography

Biographical Memoirs: Volume 71 - National Academy of Sciences (The National Academies Press, 1997)
Biographic Memoirs: Volume 71 contains the biographies of deceased members of the National Academy of Sciences and bibliographies of their published works. Each biographical essay was written by a member of the Academy familiar with the professional career of the deceased. For historical and bibliographical purposes, these volumes are worth returning to time and again.
Keywords: Biography and Autobiography

Biographical Memoirs: Volume 56 - National Academy of Sciences (The National Academies Press, 1987)
Biographic Memoirs: Volume 56 contains the biographies of deceased members of the National Academy of Sciences and bibliographies of their published works. Each biographical essay was written by a member of the Academy familiar with the professional career of the deceased. For historical and bibliographical purposes, these volumes are worth returning to time and again.
Keywords: Biography and Autobiography

Biographical Memoirs: Volume 68 - National Academy of Sciences (The National Academies Press, 1995)
Biographic Memoirs: Volume 68 contains the biographies of deceased members of the National Academy of Sciences and bibliographies of their published works. Each biographical essay was written by a member of the Academy familiar with the professional career of the deceased. For historical and bibliographical purposes, these volumes are worth returning to time and again.
Keywords: Biography and Autobiography

Biographical Memoirs: Volume 47 - National Academy of Sciences (The National Academies Press, 1975)
Biographic Memoirs: Volume 47 contains the biographies of deceased members of the National Academy of Sciences and bibliographies of their published works. Each biographical essay was written by a member of the Academy familiar with the professional career of the deceased. For historical and bibliographical purposes, these volumes are worth returning to time and again.
Keywords: Biography and Autobiography

Biographical Memoirs: Volume 53 - National Academy of Sciences (The National Academies Press, 1982)
Biographic Memoirs: Volume 53 contains the biographies of deceased members of the National Academy of Sciences and bibliographies of their published works. Each biographical essay was written by a member of the Academy familiar with the professional career of the deceased. For historical and bibliographical purposes, these volumes are worth returning to time and again.
Keywords: Biography and Autobiography

Biographical Memoirs: Volume 77 - National Academy of Sciences (The National Academies Press, 1999)
Biographic Memoirs: Volume 77 contains the biographies of deceased members of the National Academy of Sciences and bibliographies of their published works. Each biographical essay was written by a member of the Academy familiar with the professional career of the deceased. For historical and bibliographical purposes, these volumes are worth returning to time and again.
Keywords: Biography and Autobiography

Memorial Tributes: Volume 24 - National Academy of Engineering (The National Academies Press, 2022)
This is the twenty-fourth volume in the Memorial Tributes series compiled by the National Academy of Engineering as a personal remembrance of the lives and outstanding achievements of its members and international members. These volumes are intended to stand as an enduring record of the many contributions of engineers and engineering to the benefit of humankind. In most cases, the authors of the tributes are contemporaries or colleagues who have personal knowledge of the interests and engineering accomplishments of the deceased.
Keywords: Biography and Autobiography

Biographical Memoirs: Volume 46 - National Academy of Sciences (The National Academies Press, 1975)
Biographic Memoirs: Volume 46 contains the biographies of deceased members of the National Academy of Sciences and bibliographies of their published works. Each biographical essay was written by a member of the Academy familiar with the professional career of the deceased. For historical and bibliographical purposes, these volumes are worth returning to time and again.
Keywords: Biography and Autobiography

Biographical Memoirs: Volume 51 - National Academy of Sciences (The National Academies Press, 1980)
Biographic Memoirs: Volume 51 contains the biographies of deceased members of the National Academy of Sciences and bibliographies of their published works. Each biographical essay was written by a member of the Academy familiar with the professional career of the deceased. For historical and bibliographical purposes, these volumes are worth returning to time and again.
Keywords: Biography and Autobiography